Melatonin protects against gentamicin-induced nephrotoxicity in rats - ŞENER, GÖKSEL; ELÇİOĞLU, HATİCE KÜBRA (My University, 2002)
Acute renal failure is a major complication of gentamicin (GEN), which is widely used in the treatment of gram-negative infections. A large body of in vitro and in vivo evidence indicates that reactive oxygen metabolites (or free radicals) are important mediators of gentamicin nephrotoxicity. In this study we investigated the role of free radicals in gentamicin-induced nephrotoxicity and whether melatonin, a potent antioxidant could prevent it. For this purpose female Sprague-Dawley rats were given intraperitoneally either gentamicin sulphate (40 mg/kg), melatonin (10 mg/kg), gentamicin plus melatonin or vehicle (control) twice daily for 14 days. The rats were decapitated on the 15th day and kidneys were removed. Blood urea nitrogen (BUN) and creatinine levels were measured in the blood and malondialdehyde (MDA) and glutathione (GSH) levels, protein oxidation (PO) and myeloperoxidase (MPO) activity were determined in the renal tissue. Gentamicin was observed to cause a severe nephrotoxicity which was evidenced by an elevation of BUN and creatinine levels. The significant decrease in GSH and increases in MDA levels, PO and MPO activity indicated that GEN-induced tissue injury was mediated through oxidative reactions. On the other hand simultaneous melatonin administration protected kidney tissue against the oxidative damage and the nephrotoxic effect caused by GEN treatment.
Keywords: Female; Animals; Rats; Melatonin; Glutathione; Malondialdehyde; Peroxidase; Kidney; Rats, Sprague-Dawley; Gentamicins; Acute Kidney Injury